The Influence of Work Discipline on Employee Performance at Adiwana Bisma Ubud Hotel - Made Ryan Sujirmantara; Irene Hanna H. Sihombing; Ni Made Suastini (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study aims to determine the effect of work discipline on the performance of Adiwana Bisma Hotel employees analyzed using the Statistical Program for Social Science (SPSS). The type of data needed by researchers is quantitative data with an experimental research approach. This survey involved 42 employees, supervisors, and managers. This study took a sample of 42 people. Data were collected through questionnaires and assessed for validity, reliability, classical assumption tests, and basic linear regression. At the Adiwana Bisma Ubud Hotel, work discipline significantly improves staff performance.